Biodefense Research Methodology and Animal Models, 2nd edition - Swearengen, James R. (CRC Press, 2020)
Significant advances have been made in animal model development for biological research since the publication of the first edition of this volume, and the ramifications of the FDA's Animal Efficacy Rule have become better understood in the scientific community.